2021
DOI: 10.1007/s12221-021-0201-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thermo-mechanical and Morphological Properties of Jute Fabric Reinforced Epoxy/AESO Bio-composites

Abstract: In this study, the effect of curing applied to jute woven fabric (four-layers) reinforced composite materials in which different proportions of acrylated epoxidized soybean oil (AESO) and epoxy resin are used as matrix material, on the thermal, thermo-mechanical and morphological properties of the composite materials are investigated. Composite material production is carried out by vacuum infusion method, whereas curing at 90 °C is done during production and post-curing at 120 °C is performed using a condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This indicates the fact that natural fibers have different chemical bonding characteristics than synthetic fibers and they do not form a good bond with the matrix. [ 50 ] In this case, one of the reasons for the B8A4 sample having significantly less tensile strength than the C9 sample can be expressed by the bonding characteristics of the fibers. In Figure 5E,F, the structure of the A4B8 hybrid composite material is presented.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the fact that natural fibers have different chemical bonding characteristics than synthetic fibers and they do not form a good bond with the matrix. [ 50 ] In this case, one of the reasons for the B8A4 sample having significantly less tensile strength than the C9 sample can be expressed by the bonding characteristics of the fibers. In Figure 5E,F, the structure of the A4B8 hybrid composite material is presented.…”
Section: Resultsmentioning
confidence: 99%
“…By the time the JE structures in Figure 15 are checked against the JE structures in Figure 9 and Figure 12, it was found that the gaps between the matrix resin and the fibers increased. This can be expressed by the fact that natural fibers and matrix structures have different chemical structures and do not form a good bond between them [30]. In the comparison of BE structures in Figure 13 and Figure 16, it was seen that the resin did not completely cover the matrix in BE structures that were post-cured at 90 °C, indicating that there was not as much bonding between the matrix and the resin as in BE structures that were post-cured at 70 °C.…”
Section: Sem Analysis Resultsmentioning
confidence: 99%
“…The impact strength, on the other hand, had the highest value when the post curing temperature was at 80°C, while its increase from this temperature negatively affected the impact strength. It has also been found that the post-curing process improves the ratio of the material's loss modulus to the storage modulus, resulting in the development of the fiber matrix interface [30]. The effects of various operating temperatures during production were investigated, although the effects of different curing temperatures have been discussed in previous studies, it was found that the study on the effects of post-curing on tensile strength, hardness, and water absorption values of Jute and Basalt fibers and their hybrid composites is lacking in the literature.…”
Section: Introductionmentioning
confidence: 99%